ORCHESTRATING THE CLOUD: AI-ENHANCED RELEASE AUTOMATION IN KUBERNETES ENVIRONMENTS - Sekhar Chittala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Cloud-native architectures have revolutionized software deployment, necessitating advanced release automation strategies to manage increasingly complex environments. This article explores the synergy between Kubernetes and artificial intelligence in facilitating scalable, self-healing, and optimized deployments for cloud-native applications. We present a comprehensive framework for implementing automated deployment pipelines within Kubernetes clusters, leveraging its native features for horizontal scaling and rolling updates. The integration of AI-driven tools for predictive scaling, anomaly detection, and performance optimization is examined, with a focus on enhancing monitoring and rapid issue resolution. Through case studies of large-scale implementations across e-commerce, financial services, and SaaS sectors, we demonstrate the transformative impact of these technologies on release automation. Our findings reveal significant improvements in deployment efficiency, resource utilization, and system reliability. We also discuss emerging trends, including serverless deployments and edge computing, providing insights into the future landscape of cloud-native release automation. This article contributes to the growing body of knowledge on DevOps practices in cloud environments and offers practical strategies for organizations seeking to enhance their deployment processes in the era of distributed systems.